Relevance of Comet Assay and Phosphorylated-Hsp90α in Cancer Patients' Peripheral Blood Leukocytes as Tools to Assess Cisplatin-based Chemotherapy Clinical Response and Disease Outcome - Sottile, Mayra L; Gómez, Laura C; Redondo, Analía; Ibarra, Jorge; García, María B; Gonzalez, Lucía; Vargas-Roig, Laura M; Nadin, Silvina B (The journal of histochemistry and cytochemistry, 2024)
Cisplatin (cPt) is a commonly used treatment for solid tumors. The main target of its cytotoxicity is the DNA molecule, which makes the DNA damage response (DDR) crucial for cPt-based chemotherapy. Therefore, it is essential to identify biomarkers that can accurately predict the individual clinical response and prognosis. Our goal was to assess the usefulness of alkaline comet assay and immunocytochemical staining of phosphorylated Hsp90α (p-Hsp90α), γH2AX, and 53BP1 as predictive/prognostic markers. Pre-chemotherapy peripheral blood leukocytes were exposed to cPt in vitro and collected at 0, 24 (T24), and 48 (T48) hr post-drug removal. Healthy subjects were also included. Baseline DNA damage was elevated in cancer patients (variability between individuals was observed). After cPt, patients showed increased γH2AX foci/nucleus (T24 and T48). Both in healthy persons and patients, the nuclear p-Hsp90α and N/C (nuclear/cytoplasmic) ratio augmented (T24), decreasing at T48. Favorable clinical response was associated with high DNA damage and p-Hsp90α N/C ratio following cPt. For the first time, p-Hsp90α significance as a predictive marker is highlighted. Post-cPt-DNA damage was associated with longer disease-free survival and overall survival. Our findings indicate that comet assay and p-Hsp90α (a marker of DDR) would be promising prognostic/predictive tools in cP-treated cancer patients.